2017
DOI: 10.1002/jor.23790
|View full text |Cite
|
Sign up to set email alerts
|

“Patient reported outcomes” following experimental surgery—using telemetry to assess movement in experimental ovine models

Abstract: Many potential treatments for orthopedic disease fail at the animal to human translational hurdle. One reason for this failure is that the majority of pre‐clinical outcome measurements emphasize structural changes, such as gross morphology and histology, and do not address pain or its alleviation, which is a key component of treatment success in man. With increasing emphasis on “patient reported outcome measurements (PROM)” in clinical practice, in this study we have used two different telemetric methods (geol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Use of telemetry and geolocation using movement trackers was effective at assessing pain in sheep with induced osteoarthritis [ 77 ]. In addition, stride length and number of steps were good indicators of post-castration pain in cattle [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Use of telemetry and geolocation using movement trackers was effective at assessing pain in sheep with induced osteoarthritis [ 77 ]. In addition, stride length and number of steps were good indicators of post-castration pain in cattle [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…pentobarbitone sodium at 2, 4, and 6 weeks post-surgery. A semiquantitative histological analysis using International Cartilage Repair Society macroscopic score was carried out blindly as previously established 5 .…”
Section: Methodsmentioning
confidence: 99%
“…The thinner cartilage in rodents restricts the amount of damage that can be induced, and therefore is less translatable to the human disease. In contrast, large animals, such as sheep, have a similar cartilage volume (359 mm 3 ) to humans and OD can successfully be induced in their joints as evidenced by histological scoring and reduced activity 4,5 . Consequently, the majority of OD research is focused on developing strategies for bone and cartilage regeneration, such as implantation of biomaterials in large animal models 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Simpler methods have also been developed to quantify force applied by each limb using pressure mat systems ( Uilenreef et al, 2019 ) or force plates on treadmills ( Belshaw et al, 2016 ). Additionally, telemetry based analysis of distance travelled in freely moving animals has also shown promise for evaluating pain behavior in sheep ( Newell et al, 2018 ). Besides lameness, inflammation is another widely assessed in vivo outcome in arthritis models, although it should be noted that although inflammation and pain often occur concomitantly, inflammation can occur in the absence of pain and vice versa ( Bedson and Croft, 2008 , Salaffi et al, 2018 ).…”
Section: Naturally Occurring and Models Of Arthritis In Large Animalsmentioning
confidence: 99%
“…The field of large animal research has used, and continues to rely mostly on, histological analysis of joints using a modified Mankin or O’Driscoll scoring system ( Abdalmula et al, 2014 , Haak et al, 1996 , Naujokat et al, 2019 , Newell et al, 2018 ), often accompanied by protein level immunoprecipitation of inflammatory mediators such as prostaglandins E2 (PGE2), IL-6 and IL-1 β, TNF- α in the serum, synovial fluid and/or synovium tissue ( Barrachina et al, 2016 , Neuenschwander et al, 2019 , Owens et al, 1996 ). A handful of studies have also revealed expression of pain-related proteins (e.g.…”
Section: In Vitro Models To Study Peripheral Mechanisms Of Amentioning
confidence: 99%